Serotonin transporter and BDNF polymorphisms interact to predict trait worry - Bredemeier, Keith (2014)
Excessive worry is associated with a range of psychological disorders. While previous studies have examined genes associated with a range of different anxiety phenotypes, none have explored genes specifically associated with the general tendency to worry. The present study tested associations between trait worry and functional polymorphisms of three candidate genes: the serotonin transporter-linked polymorphic region (5-HTTLPR) of the SLC6A4 gene, the Val66Met region of the brain-derived neurotrophic factor (BDNF) gene, and the Val158Met region of the catechol-O-methyltransferase (COMT) gene. A heterogeneous sample of adult participants (n = 173) completed the Penn State Worry Questionnaire (PSWQ) and provided DNA samples for genotyping. Results revealed a significant interaction between 5-HTTLPR and BDNF genotypes predicting levels of worry. Specifically, there was a significant positive association between 5-HTTLPR short alleles and PSWQ scores, but only in BDNF met allele carriers. COMT genotype was not significantly associated levels of worry, nor did COMT interact with 5-HTTLPR or BDNF genotypes to predict PSWQ scores. These findings provide preliminary evidence about the putative genetic etiology of worrying. Key limitations of the present study and corresponding directions for future research on this topic are discussed.